Integrando conhecimentos sobre peixes e serviços ecossistêmicos nos recifes e Amazônia brasileira - Severo, Luiza Waechter (2024)
In aquatic ecosystems, fish species perform essential ecosystem functions crucial for the balance and functioning of these environments. Additionally, these fish are vital for the well-being and survival of human populations, providing various ecosystem services of great economic value. In Brazil, reef fish are threatened by anthropogenic impacts. Similarly, fish populations in the Amazon already show such negative effects, from small streams to large rivers. Despite the importance of these species, their aesthetic contributions to tourism, their ecological and aesthetic values both in and out of water (through fishing), as well as their functional and nutritional contributions, are still underestimated in tropical aquatic systems. This thesis, structured in three chapters, (i) calculates the aesthetic value of 82 reef fish species and reef landscapes and constructs an aesthetic index for Brazilian reefs; (ii) analyses the congruence of ecological value (i.e., C, N, and P flux (g/day)), aesthetic and economic value as fishery products (i.e., average price per kilogram in Brazilian reais) of 169 reef fish species according to landing data from Florianópolis (SC), Ilhabela (SP), Arraial do Cabo (RJ), and Guarapari (ES); and (iii) evaluates the relationship between body size and nutrients, measures the negative effects of species declines on the diversity and functional and nutritional uniqueness of 407 reef species and 59 freshwater species, respectively, and finally analyses the nutritional profiles of the fish using the daily recommended nutritional values by the FAO. In the first chapter, the results revealed that a total of 320 users have similar aesthetic perceptions of reefs, among them researchers (n=47), tourists (n=140), fishers (n=43), and divers (n=90). Predators, fish schools, and exposed reefs were the most valued landscape components. Furthermore, the biogenic reefs of northeastern Brazil exhibited the highest aesthetic values. In the second chapter, our analyses showed a positive congruence between the ecological, aesthetic, and economic values of the four studied reefs. Even using different local fish biomass and abundance values, it was evident that ecological and aesthetic values are congruent, highlighting the importance of these species for reef functioning and tourism. The third chapter revealed that smaller fish presented higher values of calcium and zinc in both ecosystems, while marine species also showed higher values of vitamin A. The removal of larger species will primarily affect the diversity and nutritional uniqueness of these ecosystems. Meanwhile, the removal of smaller species will lead to functional erosion. Finally, the species that contribute most to the FAO values are not those with the highest landings in tropical aquatic ecosystems. Our thesis reveals the importance of incorporating aesthetic value into conservation initiatives with the potential to enhance the capacity to maintain cultural services. Moreover, it is essential to assess and contrast the ecological, aesthetic, and economic values of species to develop adequate management and conservation strategies aimed at maintaining the sustainability of nature's services. This is important because, despite aiding in healthy eating, fish species, regardless of their size, are crucial for the maintenance of these ecosystems.